Perspectives on Digital Competencies in University: What’s Ahead for Education? - Huamán-Romaní, Yersi-Luis; Palacios Garay, Jessica Paola; Gutierrez Gómez, Edgar; Zata Pupuche, Pedro Enrique; Fernández Atho, Manuel Octavio; Núñez Fernandez, Anderson (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Digital competencies were part of online education and now when returning to the classroom what will happen or what we expect for the future in education. The objective is to analyze and describe the perspectives of the level of digital competence, the non-experimental descriptive quantitative methodology is used with 1987 university students. Resulting that the instrument adapted to the Peruvian version is adequate according to statistics such as Cronbach's Alpha. Concluding that the digital competences improved the academic quality and have a good level. Society is waiting for the next step to know what is presented to us in education.